2008
DOI: 10.1086/587631
|View full text |Cite
|
Sign up to set email alerts
|

Using Extremeness Aversion to Fight Obesity: Policy Implications of Context Dependent Demand

Abstract: The authors would like to especially thank Kelly Davis and Greg Allenby for their research contributions. Additionally, the authors thank Bob Clemens and Preyas Desai for their helpful suggestions and comments. 3Obesity is now a global problem. Within the U.S., the rise in obesity has been largely driven by the increase in caloric consumption. Suggested solutions for decreasing consumption have included information provision and taxation on fast food. We investigate a third option that takes advantage of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 52 publications
4
84
0
3
Order By: Relevance
“…Following prior research on contexts effects (see Sharpe et al, 2008), the only information available to participants about the food was the focal attribute -calories per serving -and the price. The respondents were instructed to look through the options and to indicate which food item they would select in each of seven food categories.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…Following prior research on contexts effects (see Sharpe et al, 2008), the only information available to participants about the food was the focal attribute -calories per serving -and the price. The respondents were instructed to look through the options and to indicate which food item they would select in each of seven food categories.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…First, we know that the negative long-term consequences of indulgence impact consumers in a number of ways, as reflected in consumer overspending (Baumeister 2002), weight gain and obesity (Sharpe, Staelin, and Huber 2008;Wang and Beydoun 2007), superfluous materialism (Ordabayeva and Chandon 2011), and addiction (Grant et al 2010). Second, consumers know they are susceptible to the negative consequences of indulgence (Cochran and Tesser 1996;Polivy and Herman 1985).…”
Section: Sadness and A Hedonic Eating Goalmentioning
confidence: 99%
“…For example, if the size of a food portion is doubled, people usually report this increase to be only around 50 to 70%. This bias is associated with higher likelihood of food overconsumption, especially because of the increasingly widespread offers of larger package sizes which are more profitable for food marketers (Chandon & Wansink, 2012).In contrast to the absolute account, evidence from both cognitive (e.g., Stewart, Brown, & Chater, 2005) and consumer psychology (e.g., Sharpe et al, 2008) has suggested that people evaluate size in relative terms -that is, people are highly sensitive to the context in which an evaluation (or a choice) is made. An individual product (e.g., a cereal bar, a ready meal) is evaluated with reference to other products (e.g., other cereal bars, other ready meals) available in the decision-making context -these can be labeled as effects of the immediate context.…”
mentioning
confidence: 99%